2008
DOI: 10.1001/archpedi.162.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems in Children With Attention-Deficit/Hyperactivity Disorder

Abstract: Sleep problems in children with ADHD are common and associated with poorer child, caregiver, and family outcomes. Future research needs to determine whether management of sleep problems can reduce adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
278
3
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(300 citation statements)
references
References 37 publications
9
278
3
10
Order By: Relevance
“…For example, Moreau et al (2014) found that youth with comorbid ADHD and anxiety had the longest sleep onset delay, shortest sleep duration, and greatest daytime sleepiness in comparison to typically developing youth or youth with ADHD alone. In addition, Sung et al (2008) found comorbid conduct problems to be a strong predictor of sleep problems in youth with ADHD. Interestingly, Lycett et al (2014) recently found that it was not the presence of either an internalizing or externalizing comorbidity but rather the presence of both an internalizing and externalizing comorbidity that was associated with increased sleep problems among children with ADHD.…”
Section: Example Psychosocial Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Moreau et al (2014) found that youth with comorbid ADHD and anxiety had the longest sleep onset delay, shortest sleep duration, and greatest daytime sleepiness in comparison to typically developing youth or youth with ADHD alone. In addition, Sung et al (2008) found comorbid conduct problems to be a strong predictor of sleep problems in youth with ADHD. Interestingly, Lycett et al (2014) recently found that it was not the presence of either an internalizing or externalizing comorbidity but rather the presence of both an internalizing and externalizing comorbidity that was associated with increased sleep problems among children with ADHD.…”
Section: Example Psychosocial Factorsmentioning
confidence: 99%
“…Taken together, studies examining sleep and comorbidity in ADHD samples point to potential bidirectional associations. However, all of these studies were conducted in school-aged children/young adolescents Hansen et al 2011Hansen et al , 2014Lycett et al 2014a, b;Moreau et al 2014) or in samples with a wide age range (ages 5/6-18) (Accardo et al 2012;Sung et al 2008), leaving it unclear how sleep and mental health are interconnected in youth with ADHD during middle and older adolescence when rates of certain mental health problems such as conduct disorder (Merikangas et al 2010), substance use , and depression/ suicidal ideation (Hinshaw et al 2012) are higher. Further, aside from the recent 1-year longitudinal studies by Becker et al (2014) and Lycett et al (2014a), all of the studies completed to date have been cross-sectional, leaving it unclear if comorbidities predict increases in sleep problems (and vice versa) over longer developmental periods or whether comorbid mental health symptoms differentially impact the sleep of adolescents with and without ADHD.…”
Section: Example Psychosocial Factorsmentioning
confidence: 99%
“…Children with ADHD have more sleep problems compared with their peers [3]. Their parents report sleep problems in 25-55% [4] and the prevalence of sleep problems, such as falling asleep and maintaining sleep, can vary between 55% and 74% [5][6][7]. The primary sleep disorder symptoms are resistance against sleep, an increase in the amount waking at night, and sleepiness during the day [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported symptoms of children and the parents are resistance against sleeping and sleeponset insomnia [8]. The increase in sleep disorders in these children is associated with the increase in ADHD symptoms [10] and weakening in functionality of the child and the family [7]. However, sleep problems may develop without any biologic symptoms, the reason may be due to the high numbers of undiagnosed sleep problems in children with ADHD compared with healthy children [11].…”
Section: Introductionmentioning
confidence: 99%
“…Keeping a job and caring for a child with a mental disorder was pointed out in two articles as an impossible task by many caregivers due to the difficulty of being on time or to high needs of children, making care very expensive (11,15) .…”
Section: Discussionmentioning
confidence: 99%